Integration of Marine and Land-based Spatial Planning: A Systematic Review of Global Trends, Challenges, and Best Practices for the Indonesian Context - Radiwan Helmi; Kiky Permana Setiawan (UIR PRESS, 2025)
Integrating marine and land-based spatial planning is a strategic priority for Indonesia, the world's largest archipelagic country. Yet, its implementation is hampered by institutional challenges such as sectoral egos and overlapping jurisdictions. This study aims to bridge the gap between conceptualization and practical implementation by conducting a systematic literature review of 22 relevant global studies from the Scopus database up to August 3, 2025. Bibliometric analysis confirms a significant gap between the conceptual understanding of